Extended Anticoagulation for Prevention of Recurrent Venous Thromboembolism in Carriers of Factor V Leiden - Marchetti, Monia; Pistorio, Angela; Barosi, Giovanni (Thrombosis and Haemostasis, 2000)
There is much debate over the appropriateness of prescribing prolonged anticoagulation to heterozygous carriers of factor V Leiden suffering a first episode of deep vein thrombosis (DVT). We, thus used meta-analysis to estimate from six eligible studies the summary odds-ratio of recurrent DVT in carriers of factor V Leiden versus noncarriers: 1.36 (CI, 1.05–1.78). After that, we used a decision model to compare lifelong costs and benefits of 6 months standard anticoagulation with those of screening for carriers of factor V Leiden and extending for 2 years their anticoagulation. Screening was a cost-effective strategy, since it provided 2 additional quality-adjusted days of life per patient at the cost of $ 12,833 per quality-adjusted year of life saved, as compared to standard management. However, screening was not costeffective in patients who were predicted to incur fatal bleeding at a rate higher than 0.34% per year or recurrent DVT at a rate lower than 9% in the first 2 years. The screening policy was cost-saving if restricted to patients with idiopathic DVT and compliant to warfarin therapy.
Keywords: Venous thromboembolism; cost-effectiveness analysis; decision analysis; factor V Leiden